Supply-side dynamics of chickpeas and pigeon peas in India - Inbasekar, Kalimuthu; Roy, Devesh; Joshi, Pramod Kumar (International Food Policy Research Institute, 2015)
This study was undertaken to analyze the dynamics of production for pulses in India, one of the most important crops in India from the perspective of nutrition as well as environmental sustainability. India has been persistently deficient in pulses in spite of significant investment by the government over time. Using secondary data for a long period of time, from 1950 to 2011, we study how production of pulses has changed across regions and over time in India. Realizing the role of pulses in the cereals complex, the study shows the changing scenario in pulses production as it was crowded out by cereals with the advent of Green Revolution technologies. We create typologies of different phases in the evolution of production in India. Results show that there have been pronounced movements in pulses, with production centers shifting regionally from north to south and east to west and some concentration in central India. Notwithstanding the turnaround in pulses in the past three to four years, pulses have been moving increasingly to marginal unirrigated areas. The econometric results based on fixed-effects estimation establish that as irrigation becomes available there is a switch away from pulses toward competing crops. Recent advances in technology with short- to extra-short-duration varieties that fit into cereal-based systems have opened up new avenues for pulses reflected in increasing production. Also, we find no evidence of crowding out of domestic production because of liberalized trade, which has been the case in pulses for a long period of time.